Logopedic rehabilitation of patients after surgical treatment of malignant tumors of the oropharyngeal zone - A. M. Stepanova; T. A. Petrova; G. A. Tkachenko; S. O. Podvyaznikov (Опухоли головы и шеи)
The most severe consequences of surgical treatment of malignant neoplasms of the oropharyngeal zone are both violations of the breathing, swallowing, chewing functions, and complete or partial loss of speech. Logopedic rehabilitation of patients with tumors of the oropharyngeal zone plays an important role in the postoperative period, as it is aimed at restoring of all of the above functions.Restoration of the swallowing function is possible due to the restoration of the motor function of preserved anatomical structures, as well as the mobility of transplanted tissues with adequately performed plastic.To restore the respiratory function, it is recommended to use the following methods: coordination of inhalation and exhalation; inhalation commission which sufficient for expression; search for the optimal position of the body; the pause function and breathing exercises. Speech skills are restoring by the sound pronunciation correction. To overcome the lockjaw is the tonic spasm of the group of muscles of mastication, which leads to the mobility restriction of the temporomandibular joint, are performing the exercises, which regulate the degree of mouth opening. Also, patients are prescribed the use of the Jaw Motion Rehabilitation System TheraBite (Atos Mediсal, Sweden).